A call to action: From evolution to revolution on the Common Reporting Standard - Elisa Casi; Sara Nenadic; Mark Dinko Orlic; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
As a result of technical development and globalisation, investing abroad has become much more accessible, and thus capable of facilitating the transference of wealth and income to offshore locations with the aim of evading tax obligations at home. In this regard, the Automatic Exchange of Information (AEOI) across countries is an important weapon in the fight to undermine cross-border tax evasion. This is why, in 2014, the Organisation for Economic Co-operation and Development (OECD) launched its proposal for a global AEOI standard, the so-called Common Reporting Standard (CRS). This article provides a cross-country analysis of the national CRS laws for a sample of 41 countries with the aim of determining whether significant deviations from the original OECD Model might hinder the effectiveness of the AEOI. The authors' key recommendation to the OECD and all participating jurisdictions is to achieve a higher level of standardisation when designing the CRS locally. Furthermore, international pressure on the US to join the CRS is needed. A global AEOI system can contribute substantially to the fight against cross-border tax evasion only if all attractive locations for illicit financial flows are eliminated.
Additional information: This material was first published by Thomson Reuters, trading as Sweet & Maxwell, 5 Canada Square, Canary Wharf, London, E14 5AQ, in the British Tax Review as Casi, Nenadic, Orlic, Spengel "A call to action: from evolution to revolution on the common reporting standard" [2019] (2) BTR 166-204 and is reproduced by agreement with the publishers.
Keywords: F42; G21; H26; H31; 330; Automatic Exchange of Information; Tax Evasion; Offshore Locations; Common Reporting Standard